Attedance System with Face Recognition Based on Raspberry Pi using Viola Jones Algorithm - Hakim, Arief Rahman (Universitas Islam Sumatera Utara, 2024)
In the process of recording attendance at the company, there are many ways that can be used, such as using an attendance card, employee ID (Identity) and fingerprints. However, the existing methods still have the potential for fraud to occur, such as entrusting attendance cards or ID cards to other co-workers, manipulating time on attendance cards, doubling fingerprints etc., so we need another more precise method such as face recognition. This method was chosen because it is considered the most appropriate and very effective than other methods. This study builds a presence system using Raspberry Pi as an image processing controller, a camera to capture facial images and an ultrasonic sensor to detect the presence or absence of people, then the system will perform face recognition using Viola Jones algorithm, followed by validation where the input data will be matched with the data contained in the database and the resulting output in the form of attendance records used for recapitulation. After testing, accurate detection results were obtained when taking the right employee face data that with perpendicular position to the camera so that attendance can be recorded